2015
DOI: 10.1177/0148607115617438
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings of the 2015 ASPEN Research Workshop—Taste Signaling

Abstract: This paper summarizes research findings from six experts in the field of taste and feeding that were presented at the 2015 ASPEN Research Workshop. The theme was focused on the interaction of taste signals with those of a postingestive origin and how this contributes to regulation of food intake through both physiological and learning processes. Gastric bypass results in exceptional loss of fat mass, increases in circulating levels of key gut peptides, some of which are also expressed along with their cognate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…Older adults and obese subjects have reduced dopamine response and thus, are at particularly high risk for reward deficiency syndrome 34,35,36 . Food reward and taste are important motivators of diet and food consumption 37 , thus reward deficiency syndrome can lead to increased intake of rewarding stimuli, like sweet and fat tasting foods. Green et al, (2013) demonstrated the reward deficiency effect in the lentiform nucleus, caudate and putamen in middle aged adults 31 ; and Jacobson et al, (2017) demonstrated the effect in the nucleus accumbens, caudate and orbital frontal cortex in older adults 27 .…”
Section: Taste Function In Aging: How Best To Capture Factors That Drmentioning
confidence: 99%
“…Older adults and obese subjects have reduced dopamine response and thus, are at particularly high risk for reward deficiency syndrome 34,35,36 . Food reward and taste are important motivators of diet and food consumption 37 , thus reward deficiency syndrome can lead to increased intake of rewarding stimuli, like sweet and fat tasting foods. Green et al, (2013) demonstrated the reward deficiency effect in the lentiform nucleus, caudate and putamen in middle aged adults 31 ; and Jacobson et al, (2017) demonstrated the effect in the nucleus accumbens, caudate and orbital frontal cortex in older adults 27 .…”
Section: Taste Function In Aging: How Best To Capture Factors That Drmentioning
confidence: 99%
“…Some of the metabolic mechanisms of action that are believed to contribute to the effectiveness of bariatric surgery are changes in hunger and satiety gut hormones, bile acid signaling, gut microbiota, inulin sensitivity, and neural pathways that regulate appetite and fat storage [4]. These changes affect patients' food consumption via altered food choices, preferences, and tastes [5][6][7][8][9] and are important to how individuals achieve and sustain significant weight loss following surgery. Alterations in one's relationship with food (e.g., reasons for eating) and eating habits (e.g., unplanned snacking) from pre-to post-surgery are important components of success.…”
Section: Introductionmentioning
confidence: 99%
“…The current study describes similar catecholaminergic, GABAergic, and glutamatergic projections to rNST and suggests that these projections differentially target the subdivisions in the NST involved in consummatory and autonomic reflexes. A brief summary of a portion of these results appeared in a symposium report (Spector et al, ).…”
Section: Introductionmentioning
confidence: 99%